Tumor handling of early-stage cervical cancer: A literature analysis of villoglandular adenocarcinoma of the cervix - Dietl, Anna; Aumann, Konrad; Beckmann, Matthias (Anticancer Research, 2020)
Background/Aim: Recent studies have demonstrated the inferior overall survival outcomes of patients with early-stage cervical cancer who undergo minimally invasive surgery (MIS). One possible explanation for these unexpected results is intraoperative tumor manipulation. Materials and Methods: Considering this hypothesis, we have reviewed the literature on the oncological outcomes of patients with villoglandular adenocarcinoma (VGA) of the cervix, an uncommon variant of cervical cancer that has an excellent prognosis. Results: VGA generally presents as an exophytic mass arising from the endocervix. In a systematic review, we identified 221 patients treated surgically for VGA (FIGO stage Ia-Ib1). Of these, 11 developed recurrence, and four died. The recurrence sites in 8 cases were the pelvis (n=3), vaginal cuff (n=3), episiotomy scar (n=1), and cervix (n=1). Furthermore, 23 VGA-patients were treated by MIS, four experienced recurrence, and one died. Three intraabdominal metastases after MIS were reported. Conclusion: Excessive tumor-handling during MIS or manipulations, e.g. cervix-dilation (during delivery), can worsen the otherwise excellent prognosis.
CRIS-Team Scopus Importer:2020-06-19
Keywords: Early-stage cervical cancer; Minimal handling; Minimal invasive surgery; Review; Villoglandular adenocarcinoma of the uterine cervix